Informal learning in youth volunteer work : perspectives from the European Voluntary Service programme - Hagh Talab, Ayda (2013)
The purpose of this study is to examine the link between volunteer work and informal learning among young people. Drawing on the concepts and theories of lifelong learning, informal learning and volunteer work, and building on past research, this thesis explores the case of the European Voluntary Service (EVS), an international volunteering scheme devised by European Commission for youth between 18 and 30 years of age. Through 10 qualitative interviews with former and current EVS volunteers, this study attempts to understand the nature and main features of informal learning in EVS as well as what young people believe they have learnt in the course of their volunteering.